Differential Regulation of Smad3 and of the Type II Transforming Growth Factor-β Receptor in Mitosis: Implications for Signaling - Hirschhorn, Tal (Public Library of Science, 2012)
The response to transforming growth factor-β (TGF-β) depends on cellular context. This context is changed in mitosis through selective inhibition of vesicle trafficking, reduction in cell volume and the activation of mitotic kinases. We hypothesized that these alterations in cell context may induce a differential regulation of Smads and TGF-β receptors. We tested this hypothesis in mesenchymal-like ovarian cancer cells, arrested (or not) in mitosis with 2-methoxyestradiol (2ME2). In mitosis, without TGF-β stimulation, Smad3 was phosphorylated at the C-terminus and linker regions and localized to the mitotic spindle. Phosphorylated Smad3 interacted with the negative regulators of Smad signaling, Smurf2 and Ski, and failed to induce a transcriptional response. Moreover, in cells arrested in mitosis, Smad3 levels were progressively reduced. These phosphorylations and reduction in the levels of Smad3 depended on ERK activation and Mps1 kinase activity, and were abrogated by increasing the volume of cells arrested in mitosis with hypotonic medium. Furthermore, an Mps1-dependent phosphorylation of GFP-Smad3 was also observed upon its over-expression in interphase cells, suggesting a mechanism of negative regulation which counters increases in Smad3 concentration. Arrest in mitosis also induced a block in the clathrin-mediated endocytosis of the type II TGF-β receptor (TβRII). Moreover, following the stimulation of mitotic cells with TGF-β, the proteasome-mediated attenuation of TGF-β receptor activity, the degradation and clearance of TβRII from the plasma membrane, and the clearance of the TGF-β ligand from the medium were compromised, and the C-terminus phosphorylation of Smad3 was prolonged. We propose that the reduction in Smad3 levels, its linker phosphorylation, and its association with negative regulators (observed in mitosis prior to ligand stimulation) represent a signal attenuating mechanism. This mechanism is balanced by the retention of active TGF-β receptors at the plasma membrane. Together, both mechanisms allow for a regulated cellular response to TGF-β stimuli in mitosis.